Metaphorical reasoning - Rybarkiewicz, Dorota (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
That metaphors are a part of law seems to be commonplace nowadays. Nevertheless, the extent of their influence is not commonly acknowledged. The three types of metaphors: (1) verbal, point metaphors, (2) systemic, thinking changing, model metaphors and (3) hidden systemic, conceptual metaphors are here associated with the distinction between what is said and how it is said and between a conscious and unconscious message delivery – all of them of particular relevance to a legal discourse. Not all types of metaphors can (and should) be dispensed with. In some negative cases the only way to reduce their adverse effects is to provide tools to detect them. The definition proposed may serve this purpose. As an illustration, the paper points to some ordinary situation giving rise to metaphoric reasoning which leads to quite unpredictable (misleading) conclusions.